Intergenerational and Intragenerational Responsibility: How Does Environmental Law Deal with the Principle of Non-refoulement? - CILENTO, CINZIA (Italian Sociological Review, 2024)
While intergenerational responsibility commonly refers to the satisfaction of the needs and demands of present and future generations (Roemer, 2007), intra-generational responsibility implies the concept of justice in a broad sense, for instance equity in measured terms of quality of life, availability of essential goods and access to equal opportunities according to capabilities and resources, guaranteed to each community member (Padilla, 2002). Both definitions are increasingly finding their way into constitutional environmental law and especially within the climate change debate, but in which respect are they interconnected? How do inter- and intra-generational responsibilities approach the issue of “climate refugees” and the principle of non-refoulement? The following paper aims to investigate what are the main features of environmental inter- and intragenerational responsibility and how normative developments related to the environmental law arena are equipped to embed intergenerational equity and the principle of non-refoulement through the case study of Ioane Teitiota, a farmer of the Republic of Kiribati who emigrated from the island of Tarawa to New Zealand prompting his displacement because of climate change.